PENGAWASAN APARATUR NEGARA DALAM RANGKA MEWUJUDKAN PENYELENGGARAAN NEGARA YANG BERSIH DAN BEBAS DARI KORUPSI, KOLUSI DAN NEPOTISME - Sri Agustini, Ni Made Mitarsih; Ariawan, I Gusti Ketut (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
A democratic government, never wanted the unclean officers. One of the initialactions that can be done is supervision. From the description, the question arises iswhat can be connected between the performance of the state official to realize a cleangovernment and supervision as what to do. The research’s method that used in thispaper is analytical approach to legal concepts and laws. Therefore, this paper will bedescribe about the implementation of a clean government that can not be separatedfrom the State official itself and it is expected the state official, should always be guidedby the general principles of organization of the State. To support it, can be through bythe internal and external monitoring. In addition, it is also needs social control of thesociety.
Keywords: State Official, Supervision, Implementation , Clean Government